Mitigasi Banjir di Kelurahan Wawombalata Kota Kendari - Weka Widayati; Sawaludin Sawaludin; Anita Indriasary; Weko Indira Romanti Aulia; Saban Rahim (Universitas Halu Oleo, 2023)
The problem of flooding is still a problem that occurs in urban communities. High water intensity during the rainy season results in the potential for flooding in residential areas around the river flow. This study aims to determine flood mitigation in the Wawombalata sub-district, Kendari City. The method used in this research is survey and map overlay. The results showed that: On the flood hazard map, the area that has the highest hazard class is in the RT 5 section. Meanwhile, the flood hazard in the high class covers parts of the RT 1, RT 2, RT 3, RT 4, RT 5, RT 6 and RT 7. Overall the potential for flooding in the Wawombalata sub-district is classified as a high hazard class up to the highest class around residential areas and community housing. Flood mitigation strategies that can be carried out include: Conducting learning about disaster mitigation and outreach as well as disaster emergency simulations, maintaining the functions of vital objects/public facilities. Coordinating disaster management at the District/City level and and the Central Government. Keywords: Mitigation, Hazard, Flood, Community